Anterior versus posterior approach in traumatic thoracolumbar burst fractures deemed for surgical management: Systematic review and meta-analysis. (December 2019) - Tan, Terence; Rutges, Joost; Marion, Travis; Gonzalvo, Augusto; Mathew, Joseph; Fitzgerald, Mark; Dvorak, Marcel; Schroeder, Gregory; Tee, Jin
Highlights: The optimal surgical approach to traumatic thoracolumbar fractures is controversial. The anterior approach is associated with increased blood loss and longer duration. Radiological, neurological & functional outcomes is similar between approaches. Future studies should be prospective with precise inclusion criteria. There is an urgent need for contemporary, high quality research in this area. Abstract: Uncertainties remain regarding the optimal surgical approach in the treatment of traumatic thoracolumbar burst fractures. We aim to compare the surgical, radiological and functional outcomes in anterior versus posterior approaches in patients with traumatic thoracolumbar burst fractures deemed for surgical management. A systematic review adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was performed. Qualitative analysis and where suitable, meta -analysis were performed to compute pooled estimates of the differences between anterior and posterior approaches. A total of six studies (three observational, one prospective non-randomized trial, two randomized controlled trials) were included. There were no cases of postoperative neurological decline. Meta-analysis demonstrates a longer duration (Mean Difference (MD) + 81.68, 95% CI 39.20 to 123.16, p < 0.001) and increased estimated blood loss (MD + 426.27, 95% CI 119.84 to 732.70, p = 0.006) for the anterior approach. No difference between approaches was found regarding length of hospital stay, late postoperative kyphotic angle, construct failure rate, instrumentation revision rate, rate of return to work, and total hospital charges. Limitations include the small number of, and heterogeneity across studies. Given the similarities in neurological, radiological and functional outcomes between the two approaches, the longer duration and estimated blood loss in the anterior approach should be a point of consideration when selecting the surgical approach. There is an urgent need for contemporary, high quality research in this area.